2019
DOI: 10.1016/s0140-6736(18)31940-8
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exome sequencing analysis in fetal structural anomalies detected by ultrasonography (PAGE): a cohort study

Abstract: Summary Background Fetal structural anomalies, which are detected by ultrasonography, have a range of genetic causes, including chromosomal aneuploidy, copy number variations (CNVs; which are detectable by chromosomal microarrays), and pathogenic sequence variants in developmental genes. Testing for aneuploidy and CNVs is routine during the investigation of fetal structural anomalies, but there is little information on the clinical usefulness of genome-wide next-generation sequencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
658
16

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 525 publications
(701 citation statements)
references
References 49 publications
(36 reference statements)
27
658
16
Order By: Relevance
“…As an initial commentary, however, these cases underscore potential areas of future research including the biology behind the discordance of fetal and newborn/childhood phenotypes, and the challenges to dysmorphology‐based imaging. As a limited series, the counseling burden associated with variants of unknown significance was not addressed but is an additional area for ongoing assessment . Curation of fetal genetic variants will depend on close communication between the clinicians and testing laboratories to assist with the understanding of not only the known pathogenic variants but also those with less robust information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an initial commentary, however, these cases underscore potential areas of future research including the biology behind the discordance of fetal and newborn/childhood phenotypes, and the challenges to dysmorphology‐based imaging. As a limited series, the counseling burden associated with variants of unknown significance was not addressed but is an additional area for ongoing assessment . Curation of fetal genetic variants will depend on close communication between the clinicians and testing laboratories to assist with the understanding of not only the known pathogenic variants but also those with less robust information.…”
Section: Discussionmentioning
confidence: 99%
“…When an ultrasound abnormality is identified, chromosome microarray (CMA) is now the first‐line test . Following a normal CMA, specific gene panels and sequencing, both exome and whole genome, are often considered given data showing an improved diagnostic yield in anomalous fetuses . The combined advances in both genetic investigations and imaging are uncovering fetal phenotypes atypical from those classically associated with a newborn, child, or adult with the same genetic condition.…”
Section: Introductionmentioning
confidence: 99%
“…The disadvantages are that panel content may not be up to date with the newest disease gene discoveries because they are typically developed on the basis of information on disease genes for conditions that present after birth and not optimized for prenatal presentations. A potentially more successful strategy that we favor is genome‐wide sequencing, such as diagnostic exome sequencing, which has already shown benefit for prenatal cases with CNS abnormalities, but full investigation of the clinical utility and their place in prenatal genetic testing is still underway …”
Section: Detection Of Aneuploidies Copy Number Gains and Losses Andmentioning
confidence: 99%
“…In cohorts of all prenatal anomalies, WES has demonstrated a clear or likely diagnostic yield in 9% to 47% of cases when microarray and/or karyotype are normal . A recently published large prospective cohort study demonstrated a yield of 8.5% for diagnostic genetic variants in fetuses with a variety of structural anomalies, and the diagnostic yield specifically for the NIHF cases within this cohort was 9%. Finally, among a cohort of deceased fetuses with anomalies undergoing WES, 41% of cases with pathogenic variants, and 31% of cases with variants in candidate genes had hydrops …”
Section: Genetic Evaluation Of Nihfmentioning
confidence: 65%